Efficiency of injectable formalin- inactivated whole-cell bacterins of Vibrio harveyi vaccine in preventing vibriosis in marine red hybrid tilapia (Oreochromis spp.) - Abu Nor, Nadirah (2022)
Vibriosis is a serious illness caused by a group of bacteria called Vibrio in aquaculture industries while vaccination is an alternative method in protecting fish from diseases. However, the evaluation and testing of developed vaccines against vibriosis in real hosts are expensive and tedious to conduct especially on the laboratory scale. In addition, the use of marine tilapia in studying vibriosis was very limited and little attention was given. Thus, studying the ability and susceptibility of marine red hybrid tilapia against vibriosis and the efficacy of developed formalin-inactivated whole-cell bacterins of Vibrio harveyi (FKVh) vaccine was important. This research’s aims to develop vibriosis in marine red hybrid tilapia and to evaluate the efficacy of FKVh vaccine itself. A disease development study was conducted with 90 marine red hybrid tilapias and divided into 15 fishes per group with triplicate. Group A was infected with 2.3 x 109 CFU/mL of virulent V. harveyi inoculum and Group B was injected with phosphate buffered saline (PBS) and act as a negative control. Various organs such as the liver, brain, spleen and kidney were collected and subjected to immunoperoxidase (IP) staining for histopathology. Following infection with V. harveyi, infected fish showed some clinical signs such as inappetence and the presence of mucus in water was seen. Meanwhile, uninfected fish do not show any clinical signs. Group A showed 80% mortality after infection and group B showed 0% mortality. The distribution and intensity of brown colour using IP staining were higher in infected group A compared to uninfected group B. For the study of the immune responses, 200 marine red hybrid tilapias were used and divided equally into 2 groups with 30 fishes per group with triplicate. Group 1 was vaccinated with 100 μL of the FKVh vaccine containing 106 cells/fish on week 0 and a booster dose was administered on week 2. Group 2 was injected with 100 μL of PBS on weeks 0 and 2. Samples of skin mucus, serum, and gut lavage were collected and subjected to ELISA and lysozyme assay. The initial assessment at one week post-vaccination showed that injectable FKVh vaccine immunized fish significantly (P < 0.05) stimulated the IgM level of all samples compared to unvaccinated fish. The lysozyme activity was also significantly (P < 0.05) higher in the vaccinated group compared to the unvaccinated group and increased drastically after the vaccine was given on week 0, indicating vaccination possibly induce lysozyme activity in samples to some extent. A study of mucosal immunity in both SALT and GALT was done using 200 fishes and divided into 2 groups. Group 1 was vaccinated while group 2 was the unvaccinated group. The results showed the size and numbers of GALT and SALT in the vaccinated group were significantly (P < 0.05) higher compared to the unvaccinated group. Size, density and number of lymphocytes of GALT and SALT kept higher by weeks. Moreover, the GALT and SALT’s size and numbers of lymphocytic cells in this study were positively correlated with the elicitation of antibody (IgM) level in gut lavage in immunological assessment in the previous chapter. In the protective efficacy study of FKVh vaccine, the unvaccinated group showed high cumulative mortality (80%) compared to the vaccinated group which was only (13%). The histopathology analysis examined the presence of meningoencephalitis in the brain concurrently with haemorrhages. Kidney, spleen, gill and liver also showed severe haemorrhagic, congestion, eosinophilic granular inflammatory cells infiltration, necrosis, vacuolation, haemosiderin deposition, melanomacrophages aggregations, hypercellularity and fusion of secondary lamella. Combining our results demonstrate that FKVh vaccine could elicit significant innate and adaptive immunological responses against V. harveyi in marine red hybrid tilapia. This vaccine is highly effective to control vibriosis in marine red hybrid tilapia as tilapia is well-known as a freshwater fish. Besides, marine tilapia also can be the best candidate for the fish model in studying marine bacterial diseases. Therefore, this vaccine can effectively protect marine tilapia against vibriosis and also could offer a promising strategy for an effective therapeutic measure in the aquaculture industry.